Finnish Mathematics Teachers Talk about Restructuring Practice - Ann-Sofi Röj-Lindberg (Networks: An Online Journal for Teacher Research, 2013)
The case study presented in this article addresses how five Finnish mathematics teachers, colleagues in a Swedish speaking teacher training school, talked about on-going restructuring of their teaching and learning practices in terms of experiences and expectations five months into an action research process that they initiated in the early 1990s. In this action research the teachers were the agents of change (Leder, 1989); I joined the process as an outsider researcher.